Scientometric Analysis of Research Publications of National Institutes of Technology - Shettar, Iranna M.; Hadagali, Gururaj S. (Journal of Information and Knowledge, 2020)
The study examines the research productivity of the National Institutes of Technology established in India. Further it ranks the NITs based on TP, TC, ACPP, h-index, Impact of Collaboration, Impact of Internationally collaborated publications, authorship pattern etc. To retrieve the data, Web of Science database was used for the period from 2009 to 2018. The results of the study suggest that NIT Rourkela and NIT Trichy are the most prominent institutions among all the NITs. It was also observed that papers involving international collaboration receive comparatively more citations.